Phase II dose titration study of regorafenib in progressive unresectable metastatic colorectal cancer - Takeshi Kato; Toshihiro Kudo; Yoshinori Kagawa; Kohei Murata; Hirofumi Ota; Shingo Noura; Junichi Hasegawa; Hiroshi Tamagawa; Katsuya Ohta; Masakazu Ikenaga; Susumu Miyazaki; Takamichi Komori; et al. (Scientific Reports, 2023)
Abstract Regorafenib has shown significant survival benefit as a salvage therapy for colorectal cancer; however, its starting dose has been controversial in recent studies. Therefore, we conducted a prospective study on the efficacy and safety of the dose reduction of regorafenib to 120 mg. Patients received 120 mg regorafenib once per day for 3 weeks, followed by a 1-week off-treatment period. The primary endpoint was the investigator-assessed disease control rate (DCR). Sixty patients were registered, and the DCR was 38.3% with a median progression-free survival of 2.5 months (95% confidence interval [CI] 1.9–3.7) and median overall survival of 10.0 months (95% CI 6.9–15.2). Common grade 3–4 adverse events were hand-foot skin reaction and hypertension (20.0% each). The results of administration of 120 mg regorafenib as the starting dose are consistent with reports from prior phase III trials, which used starting doses of 160 mg. This lower initiating dose of regorafenib may be beneficial to certain patient populations. This clinical trial was registered in the UMIN Clinical Trials Registry (UMIN-CTR number UMIN000018968, registration date: 10/09/2015).